Studying the Relationship between Green Supply Chain Management Dimensions and Improve Healthcare Quality Service: An Empirical Study - Ahmed , Esraa; El- Sayed, Khaled (The Arab Journal of Administration, 2023)
Research Objective: The research aims to identify the practices of green purchase management and investigate the extent of their comprehensiveness or limitations. This is in addition to identifying its impact on improving the quality of services provided in university hospitals in Greater Cairo Governorate. Research Methodology: In order to obtain the primary data related to the study variables, a survey form has been prepared for sample of the workers in senior managements, management of stores, procurement management, occupational health, and safety, Scales are used to prove their validity in previous studies and how to adapt them for use in this study, as most of the studies were done in a non-Egyptian environment. To analyze the data, the researcher relies on descriptive statistics to test the study hypotheses. The findings of the study: conclude that there is a positive impact of green purchase management on improving the quality of service provided in the hospitals subject to the study. Recommendations: The study recommended that the hospital administration pay attention to increase awareness of the concept of environmental sustainability and the importance of preserving the environment and the positive effects it achieves, through holding training course.